Optimizing Student Engagement in Primary Science and Social Learning: The Feasibility of Contextual Interactive Video Media - Cok Istri Dian Natharani; Anak Agung Gede Agung; Didith Pramunditya Ambara (Jurnal Edutech Undiksha, 2024)
The lack of interactive, creative, and innovative instructional media provided by educators has resulted in students’ diminished interest and difficulty in concentrating during lessons, thereby leading to lower academic performance. This study aims to develop interactive video media based on the contextual teaching and learning approach for the topic of plant body parts in the fourth-grade science and social curriculum (IPAS) at elementary school. The research employed the ADDIE model, with data collected through observation, interviews, expert evaluations, and trial testing. Data were analyzed using quantitative descriptive analysis techniques. The results of the development of interactive video media indicate that: the design expert judgment test yielded a score of 92.05% in the "very good" category; the feasibility of the interactive video media, as evaluated by subject matter experts, achieved a score of 97.72% in the "very good" category; the scores obtained from learning design experts and media experts were 92.05% in the "very good" category, individual testing yielded a score of 93.33% in the "very good" category, and small group testing yielded a score of 89.72% in the "good" category; the effectiveness test using a correlated t-test produced t_calculated = 12.558, which is greater than t_table = 2.056 at a 5% significance level with 26 degrees of freedom, leading to the rejection of the null hypothesis (H₀) and the acceptance of the alternative hypothesis (H₁). This indicates a significant difference between pre-test and post-test scores before and after the use of the interactive video media. It can be concluded that the interactive video media product based on contextual teaching and learning is suitable for use in the learning process.